A DSR Methodology for Conceptual Solution Development of Public Open Space Governance - Gabriel Hoh Teck Ling; Pau Chung Leng; Noradila Rusli; Wai Shin Ho (Journal of Regional and City Planning, 2021)
Considering the importance of the 11th Sustainable Development Goal on sustainable cities and communities and the New Urban Agenda, it is imperative to address one of today's crucial urban planning challenges, which concerns overexploitation, mismanagement, and quality issues related to public parks and state-owned public open space (POS). Selecting an appropriate methodological framework to formulate a solution to cope with the encountered challenges is necessary; however, finding a suitable one is difficult as there is a lack of research, particularly on the step-by-step development of a conceptual countermeasure (solution). Against this background, we adopted the revised design science research (DSR) framework and its procedural methodology to formulate a conceptual solution, represented as an artifact, within the institutional-social-ecological context of Sabah, Malaysia. The data obtained for the development and validation of the solution were secondary, based on a review via content analysis of prior studies. The proposed conceptual artifact (self-governing collective action) based on the root causes (i.e. property rights and transaction costs issues) from the 'why' analysis was then validated via the institutional analysis and development (IAD) framework using its social-ecological system (SES) criteria. The main contribution of this study is to showcase the application and relevancy of the DSR framework for urban and environmental planning research through a problem-solution analysis by demonstrating the process of how the artifact was systematically constructed, validated and standardised. It was found that the proposed conceptual solution can be considered valid and appropriate to address the local governance issues of POS. Abstrak. Mempertimbangkan pentingnya Tujuan Pembangunan Berkelanjutan ke-11 tentang Kota dan Komunitas yang Berkelanjutan dan Agenda Perkotaan Baru, penting untuk mengatasi salah satu tantangan perencanaan kota yang krusial saat ini terkait dengan permasalahan eksploitasi yang berlebihan, salah kelola, dan kualitas taman maupun ruang terbuka milik publik/negara (POS). Mencari kerangka metodologi yang tepat untuk mengatasi tantangan tersebut dirasakan perlu, tetapi menemukan yang cocok masih sulit karena kurangnya penelitian, terutama tahapan dan langkah mengembangkan konsep tindakan penanggulangan. Dengan latar belakang ini, dalam konteks kelembagaan-sosial-ekologis Sabah, Malaysia, kami mengadopsi kerangka kerja Penelitian Ilmu Desain (DSR) yang telah direvisi dan metodologi proseduralnya untuk merumuskan solusi konseptual yang direpresentasikan sebagai artefak. Data yang diperoleh untuk pengembangan dan validasi solusi adalah data sekunder, berdasarkan tinjauan melalui analisis konten dari studi sebelumnya. Artefak konseptual yang diusulkan (tindakan kolektif yang mengatur diri sendiri) berdasarkan akar penyebab (yaitu, masalah hak milik dan biaya transaksi) dari analisis 'mengapa'yang  kemudian divalidasi melalui kerangka Analisis dan Pengembangan Kelembagaan (IAD) dengan menggunakan kriteria social-ecological system (SES). Kontribusi utama studi ini adalah penerapan dan relevansi kerangka DSR dalam penelitian perencanaan kota dan lingkungan melalui analisis solusi masalah, dengan menunjukkan proses bagaimana artefak dibangun, divalidasi, dan distandarisasi secara sistematis. Akhirnya, artikel ini menunjukkan bahwa solusi konseptual yang diusulkan dianggap valid dan sesuai untuk mengatasi masalah tata kelola lokal POS. Kata kunci. Ruang terbuka publik, design science research, sistem tata-kelola mandiri, ekonomi kelembagaan baru, solusi konseptual.